A Compact Planar Ultra-Wideband Array Antenna - Junli Zhu; Mengfei Chen; Ziting Li; Jingping Liu (International Journal of Antennas and Propagation)
Ultra-wideband (UWB) antennas have recently gained prominence in communication, radar technology, and electronic warfare domains. The quick development of these antennas is due to the wide bandwidth requirements of pulse radar, ground penetrating radar, electromagnetic compatibility, spaceborne communication systems, stealth target detection, and more. Aiming to address the defects of existing UWB antennas, which often have narrow bandwidth and low gain, a planar ultra-wideband microstrip array antenna was designed to achieve good ultra-wideband characteristics and effectively improve the gain of the antenna. The initial bandwidth of the rectangular monopole antenna was 10 GHz–20 GHz. After loading multiple steps on the monopole patch, the bandwidth was increased to between 10 and 38 GHz. Using the new ultra-wideband array method that combines series feed and angle feed and the defective ground structure (DGS), the array maintains the ultrawide bandwidth span of 10–38 GHz of the array element, and the maximum gain of the antenna in the bandwidth was increased from 5.18 dBi to 9.55 dBi. The challenge of impedance matching of antenna units in ultra-wideband is resolved by the novel array technique, which also increases the antenna’s gain within the bandwidth. The antenna simulation is consistent with the measurement results. With its extensive operating frequency band, high gain, compactness, and favorable radiation attributes, this newly designed antenna holds significant promise for application in UWB radar systems.